Desmitificando mitos: Análisis económico de la doble instancia en el proceso civil peruano - Núñez del Prado Chaves, Fabio (2014)
Inside the Peruvian civil process, there are warranties that seek to protect the rights of the persons who come to it. Since these warranties  are  affirmed in the   Peruvian Constitution and in international human rights treaties, they are considered as fundamental rights. One of them is the right to a second hearing.The present essay is a constructive critic of the principle of the right to appeal. The hypothesis consists in proving, through an economic analysis,  that  the  second hearing does not play a role in our legal system.